Democracy a world history - Kaplan, Temma (New Oxford World History., 2015)
This book examines the development of the democratic ideal from ancient Rome to the Cortes in Spain, the philosophies of Guru Nanak and the Castilian patriot Juan de Padilla, and such inspirational personalities as the Polish trade unionist Anna Walentnyowicz and Burmese politician Aung San Suu Kyi. Though few democracies have sustained themselves for significant lengths of time, their emergence nearly everywhere on earth over thousands of years indicates their resilience despite the fragility of the democratic ideal.